Booklet and Whatsapp monitoring for iron supplementation: Adherence and hemoglobin among rural indonesian girls - Raodhah, Sitti; Alam, Syamsul; Nurfadila, Nurfadila; Jayanti, Dwi; Jannah, Miftahul; Dirham, Nurazizan; Atthilah, Ananda Tiara (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Adolescent anemia remains a persistent public health problem despite widespread weekly iron supplementation, while evidence on integrated self-monitoring and digital adherence support in rural communities remains limited; this program evaluated a combined booklet and WhatsApp-based strategy. This community service program aimed to assess implementation of a TTD Monitoring Booklet integrated with a WhatsApp Group to support weekly iron supplementation adherence and improve hemoglobin status among adolescent girls in Dusun Bontopanno, Gowa Regency, Indonesia. A Community Development approach with a pretest–posttest design was implemented among 20 adolescent girls over 24 weeks. The intervention included anemia education, weekly tablet-consumption recording, WhatsApp reminders, motivational messages, interactive communication, and monitoring by facilitators and community health cadres. Adherence records showed that participants consumed 11–24 tablets during the intervention, with most consuming 17–23 tablets. Mean hemoglobin concentration increased from 11.83±1.04 g/dL at baseline to 13.22±0.90 g/dL after intervention (p=0.003). The proportion with hemoglobin <12.0 g/dL decreased from 45.0% to 5.0%. Integrating simple self-monitoring with accessible digital communication may provide a feasible, low-cost strategy for strengthening community-based weekly iron supplementation programs, particularly in rural and resource-limited settings.